The Significance of Philosophical Scepticism. - Stroud, Barry (Oxford University Press, 1984)
This book raises questions about the nature of philosophy by examining the source and significance of one central philosophical problem: how can we know anything about the world around us? Stroud discusses and criticizes the views of such philosophers as Descartes, Kant, J.L. Austin, G.E. Moore, R. Carnap, W.V. Quine, and others.